Peran Media Sosial Dalam Pembentukan Opini Publik: Studi Kasus Pengguna Instagram - M. Husen (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
The rapid development of social media has significantly transformed communication patterns within society, particularly in the formation of public opinion. This study aims to analyze the role of social media—specifically Instagram—in shaping public opinion through patterns of interaction, information dissemination, and meaning construction in digital spaces. Using a literature review method, this research examines theoretical and empirical findings related to political communication, social media user behavior, and the mechanisms by which public opinion is formed in the digital era. The findings indicate that Instagram functions not only as a visual-sharing platform but also as a discursive arena that influences users’ perceptions through algorithms, viral content, and the role of influencers as opinion shapers. The study further reveals that users tend to form opinions based on repeated exposure, group value alignment, and perceived credibility constructed within online communities. This study concludes that Instagram plays a strategic and complex role in shaping public opinion due to the interplay of technology, digital culture, and user communication behavior. The contribution of this research lies in mapping key factors involved in public opinion formation on social media and emphasizing the importance of digital literacy in minimizing information distortion.